Scale-dependent segregation of seeders and resprouters in cork oak (Quercus suber) forests. - Coca, M.; Pausas, J. G. (Oecologia, 2012)
Recent studies showed that disturbances and water availability determine the richness among plants with different post-fire strategies of Mediterranean-type ecosystems. The aim of this study was to determine whether or not the scale of analysis has an influence on the effects of these factors and, therefore, on the segregation of the dominant post-fire strategies, obligate seeders and obligate resprouters, and facultative species. We recorded all woody species and geographical features on 94 (75 m(2)) plots of cork oak woodlands in the southern Iberian Peninsula. For each regenerative type (resprouters, seeders and species with both traits--facultative species), we tested the relationship between the number of species and the predictors using a generalised linear mixed model. The fixed predictor considered at the large scale was altitude, and fixed predictors considered at the local scale were aspect (north/south) and disturbance (fire and clearing by heavy machinery; yes/no). The random predictor was the factor of site. When this factor did not have significant effect for some regenerative types, these relationships was tested using a generalised linear model. Resprouting species were most represented at lower altitudes and in undisturbed sites, while seeders were also at lower altitudes but mostly on south-facing slopes, especially south-facing disturbed sites. For facultative species, site is the most important variable. The proportion of seeders from the total species is not related to altitude, but it is related to disturbance and aspect. These results suggest that there is no segregation of the richness of seeders and resprouters at the large scale (altitudinal gradient). Differences appeared at the local scale (aspect and disturbance).
The following values have no corresponding Zotero field: accession-num: 21863245
Keywords: Cork oak forests; disturbance; Mediterranean vegetation; Moisture regime; Post-fire strategies

Mediterranean vegetation dynamics: modelling problems and functional types - Pausas, J. G. (Plant Ecology, 1999)
Gap models have been applied to a wide range of ecosystems, mainly temperate and boreal forests, but rarely have such models been applied to Mediterranean ecosystems. In the present review we address some problems of gap models for predicting the long-term dynamics of Mediterranean ecosystems, and we suggest plant functional types suitable for modelling based on responses to disturbance. Most gap models do not take into account different life forms, interactions with ﬁre (e.g., resprouting and stimulation of the germination), and underground structures. Long term human impact on Mediterranean ecosystems has made a signiﬁcant impact on the current landscapes. That intense land use, involving long-lived slow-growing species, has had long-term consequences. It is not possible to understand Mediterranean vegetation and to validate any model without considering these factors. The lack of data for Mediterranean species may be overcome by taking into account correlations of traits and trade-offs between different functional types. A simple disturbance-based functional group system is discussed.
Keywords: disturbance; Fire ecology; gap models; Mediterranean; resprouting